Talent Management Strategies and Their Impact on Positive Thinking Patterns Among Saudi Graduate Students at Local and Foreign Universities - Ali Alzubaidi, Ibrahim Abdah (Forum for Linguistic Studies, 2025)
The study aimed to identify language-mediated talent management strategies and their impact on positive thinking patterns among Saudi graduate students: a comparative study between local and foreign universities. To achieve the study objectives, the researcher prepared two tools: the first tool, "The Effectiveness of Talent Management Strategies," consisted of (32) paragraphs distributed across (4) areas, and the second tool," Developing Positive Thinking Patterns," consisted of (34) paragraphs distributed across (4) areas. The study sample consisted of (410) students, including (236) male students and (174) female students, who were randomly selected during the second semester (2025 AD/1446 AH). The results indicated that the arithmetic means of the effectiveness of talent management strategies were moderate, while the effectiveness of developing positive thinking patterns was high. There were no statistically significant differences between the two tools according to the gender variable, nor were there differences in the areas of (talent retention, talent development and nurturing, and talent attraction) according to the university variable. No differences were found in the areas of emotional intelligence, love of learning, and healthy cognitive openness based on the university variable. Differences were found in the area of talent management in favor of foreign universities. No statistically significant differences were found based on the college type variable for either instrument. The study recommended strengthening the culture of talent management, identifying the types of skills required, and developing a mechanism for academically developing talent and improving performance.